Individual Faces Were Not Discarded During Extracting Mean Emotion Representations - Li, Huiyun; Ji, Luyan; Li, Qitian; Chen, Wenfeng (Frontiers in Psychology, 2021)
Individuals can perceive the mean emotion or mean identity from a group of faces. It has been considered that individual representations were discarded when extracting mean representation, for example, the “element-independent assumption” asserts that the extraction of mean representation does not depend on recognizing or remembering the individual items. While the “element-dependent assumption” proposes that the extraction of mean representation is closely connected with the processing of individual items. It remains unclear on the processing mechanism of mean representation and individual representations. The present study used a classic member-identification paradigm and manipulated the exposure time and set size to investigate the effect of attentional resources allocated to individual faces on the processing of both mean emotion representation and individual representations in a set, and the relationship between the two types of representations. The results showed that when the precision of individual representations was affected by attentional resources, the precision of mean emotion representation did not change with it. Our results indicated that there might exist two different pathways for extracting mean emotion representation and individual representations, and the extraction of mean emotion representation may had priority. Moreover, we found that individual faces in a group could be processed to a certain extent even under extremely short exposure time, and the precision of individual representations was relatively poor, but not discarded.